Compatability among Varieties in Capsicum Annum L. and Frutescens L. - Krisnakumari K (Department of Olericulture, College of Horticulture, 1984)
Attempts at interspecific hybridization in the genus Capsicum have succeeded only in a few cases. Most of the crosses resulted in negligible seed set and flower fall. Capsicum frutescens is valued for its high pungency and also for the source of resistance to leaf curl and mosaic complex. An experiment was planned and carried out during 1982-83 at the Instructional Farm of the College of Horticulture, Vellanikkara, Trichur to find out crossability and related aspects involving two cultivated varieties of Capsicum annuum (Jwala and K2) and three useful lines of Capsicum frutescens (White Kanthari, Green Chuna and Ornamental Type). All crosses including directs and reciprocals were found to be compatiable except in two combinations where white kanthari was used as the female parent. Relative efficiency of hand pollination, mixed pollination and pollination after NAA (15ppm) spraying on compatibility indicated that the crosses white kanthari x Jwala and white kanthari x K2 failed with hand pollination and pollination after NAA sprying whereas these crosses were successful with mixed pollination. Effect of maternal parent on crossability index and percentage seed set efficiency was found to be significant. The chromosome numbers of the five parental lines were found to be 2n= 24. Significant heterosis was observed for many of the characters. Genetic distance reveals that parents Jwala and Green Chuna were the farthest whereas K2 and ornamental Type were the closest. Maximum oleoresin content was in Jwala (16.83%) and in hybrids Jwala x ornamental Type had the highest (16.6%).